I have a few questions and doubts...
Q1 ) Show that e^x is an increasing function of x for all x. Deduce that e^x ≥1 for x ≥0
My answer:
let f(x) = e^x
f'(x) = e^x
so if x = 0,1,2,3,etc
f'(x) > 0 therefore e^x is an increasing function
for the deduce part:
let x = 0, 1, 2,etc
e^0 =1, e^1 = 2.72, e^2 =7.4, etc
therefor e^x ≥1 for x ≥0
**Have I showed and deduced this the correct way?**
Q2) By finding the area under graphs of y=e^x and y =1 between 0 and X ,where X ≥ 0, deduce that e^X ≥1+X for X ≥0 and that (e^X) ≥ 1+X +(1/2)X^2 for X ≥0
My answer :
graph:
(y=e^x)area= {0 , X} ∫ e^x dx =e^X - e^0 = e^X - 1
(y=1)area = {0 , X} ∫ 1 dx= X
from graph area: e^X - 1 ≥ X
e^X ≥ X+1
if X = 0 e^0 ≥ 1
X=1 e^1 ≥ 2
**Is this how you deduce?**
**How can we show equation: (e^X) ≥ 1+X + (1/2)X^2 for X ≥0 ? Where did + (1/2)X^2 come from??**
**How to deduce (e^X ) ≥ 1+X +(1/2)X^2 for X ≥ 0 ??**
Q1
For the deduce part, do only for x = 0
e^0 =1
Since e^x is an increasing function as proven earlier, it follows that e^x for x≥0 will be greater or equal to e^0
Thus, e^x ≥1 (deduced)
Q2
Actually, since , you would already know that the above is true...
Because it stated "by finding the area", we can't do that. I can't see the graph from here, but this is what I would do.
Area =
= (e^x - x) from 0 to X
= e^X -X -1
Since area ≥ 0, e^X - X - 1 ≥ 0
e^X ≥ 1 + X (deduced)
Also, because e^X ≥ 1 + X, we can expect the graph of y=e^X to be above y= 1 + X
Hence, area between y=e^X and y= 1 + X
Area2 =
= (e^x - x - ½x²) from 0 to X
= e^X -X - ½X² - 1
Since Area2 ≥ 0, e^X -X - ½X² - 1 ≥ 0
Hence, e^X ≥ 1 + X + ½X² (deduced)
Regards,
Eagle
(ExamWorld)
great, just what i needed...thanks. I see what a basic deduction requires now!!
How did u put the maths equation with the proper notation of an integral? Did u make the eq. from a software and then pasted it here?? If so then which software??
few more questions...
Q1)Find stationary value of y=lnx - x and deduce that ln x ≤ x - 1 for x >0 with equality only when x = 1.
My answer:
dy /dx = 1/x -1
if 1/x -1 = 0
x=1
stationary value : y =ln 1 -1 = -1 **Isn't this correct?**
for the deduce part:
if stationary value = -1
ln x - x (** ≤ or ≥ , how to know??**) -1
ln x ≤ x - 1
therefor if x = 1 ln 1 ≤ 0 **is this deducing correct?**
Q2) By putting x = z / y where 0< y < z, deduce Napier's inequality,
1/z < (ln z - ln y) / (z - y) < 1/y
**how to deduce this one??**
A bit busy at the moment to take a closer look...
Mikethm, wee_ws, Ahm97sic, anyone of you around please help? I will be out till quite late tonight...
Originally posted by prg:
Q1)Find stationary value of y=lnx - x and deduce that ln x ≤ x - 1 for x >0 with equality only when x = 1.
My answer:
dy /dx = 1/x -1
if 1/x -1 = 0
x=1
stationary value : y =ln 1 -1 = -1 **Isn't this correct?**
for the deduce part:
if stationary value = -1
ln x - x (** ≤ or ≥ , how to know??**) -1
ln x ≤ x - 1
therefor if x = 1 ln 1 ≤ 0 **is this deducing correct?**
You found the stationary value to be -1. With 2nd derivative, we see that
d2y/dx2 = -1/x^2
When x = 1
d2y/dx2 = -ve (max pt)
lnx -x must be equal or less than -1.
Thus lnx -x ≤ -1
ln x ≤ x-1
Qn 2 you gotta wait for someone else as I totally forgot about Napier's inequalities haha... Recommend you post it into the thread where someone is offering JC Maths help. :P
Q2)
Actually.... I have never learnt Napier's inequality before (nor have I learned graphic calculators before).
But to me, I will treat it as a normal inequality to solve since that is what it is all about.
Divide by y throughout
===> This is what we need to prove
Graphical Method:
So what you can do is to use your graphic calculator now, and plot the follow graphs
y = x
y = 1
==> do it from values 1.05 to 20.
Then show that the graph lies under the graph y = x and above the graph y = 1 for values of x greater than 1
because z > y > 0, then z/y > 1, and thus x > 1
Analysis Method:
From Question 1, ln x ≤ x-1, and ln x = x -1 only at x = 1 (max point)
So for x>1, ln x < x -1
Hence, (x -1) / ln x < 1 (no need to change sign since both are positive)
Also, need to prove x>(x -1) / ln x
or x ln x > x - 1
or x ln x - x > -1
differentiate x ln x - x and set it to zero
ln x + 1 - 1 = 0
x = 1
At x = 1, x ln x - x = -1
second derivative, 1/x, when x = 1, gives 1 > 0
Hence, -1 is the minimum point
Thus, x ln x - x > -1 is proven
And thus x>(x -1) / ln x
Hence,
is proven.
Question and solutions will be added to ExamWorld later.
Regards,
Eagle
(ExamWorld)
few more questions!!
curve y=e^-2x -3x crosses x-axis at A (a,0) and y-axis at B(0,1)
Curve:
:
(a)Write down an equation satisfied by a.
if y=e^-2x -3x then x=a and y =0
**is this correct**
(b) show that tangent at A meets y-axis at point whose y-coordinates is
for eq of tangent at A if curve: y=e^-2x -3x
y - y1 =m (x - x1)
x1= a y1=0
if x= 0 (y-axis)
y-coord.: **is this the correct way??**
(c) Show that d^2 y / dx^2) >0 and using results from parts (a) and (b), deduce that 6a^2 + 3a < 1
**how to do this?**